2012
DOI: 10.1007/s00380-012-0314-x
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of periprocedural myocardial infarction and cardiac biomarker testing after percutaneous coronary intervention in Japan: results from a multicenter registry

Abstract: Periprocedural myocardial infarction (pMI) is an important complication associated with percutaneous coronary intervention (PCI). However, data on the frequency of biomarker testing and the incidence of pMI remain unclear. Using the multicenter Japan Cardiovascular Database, we identified 2182 patients who underwent PCI without preprocedural cardiac biomarker elevation (silent ischemia, stable angina, or unstable angina without biomarker elevation) from September 2008 to August 2011. Of these, 550 patients (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first cohort study investigating the predictors of DCTP. The prevalence of DCTP during a 7‐year period was found to be 12.1%, which coincides with the prevalence range of PMI worldwide (Arai et al., ; Chen et al., ; Christensen et al., ; Idris et al., ; Mäkikallio et al., ; Prasad & Herrmann, ; Tsabedze et al., ; Wessler et al., ; Yamaji et al., ). However, the interpretation of this information must be done with caution, considering the several definitions on PMI used by different studies.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first cohort study investigating the predictors of DCTP. The prevalence of DCTP during a 7‐year period was found to be 12.1%, which coincides with the prevalence range of PMI worldwide (Arai et al., ; Chen et al., ; Christensen et al., ; Idris et al., ; Mäkikallio et al., ; Prasad & Herrmann, ; Tsabedze et al., ; Wessler et al., ; Yamaji et al., ). However, the interpretation of this information must be done with caution, considering the several definitions on PMI used by different studies.…”
Section: Discussionsupporting
confidence: 70%
“…After PCI, an elevation of cardiac biomarkers above three times their basal values is expected (CathPCI Registry, ). However, periprocedural myocardial infarction (PMI) after PCI, remains a common complication in 2.6–38.8% of cases worldwide (Arai et al., ; Chen et al., ; http://Christensen, http://Huang, http://Torp-Pedersen, http://Trydal, & http://Ravkilde, ; Idris et al., ; Mäkikallio et al., ; Prasad & Herrmann, ; Tsabedze et al., ; Wessler et al., ; Yamaji et al., ).…”
mentioning
confidence: 99%
“…1,11 The frequency of PMI was lower in some studies, which were not measured cardiac biomarkers in all patients after PCI. 12 We routinely measured cardiac biomarkers before, at 8, and at 24 hours after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the number of patients undergoing PCI for coronary artery disease has been increasing rapidly, according to many medical reports from all over the world. However, many studies have demonstrated that periprocedural myocardial infarction (PMI) is a vital and frequent complication for patients undergoing PCI, which was assessed by quantitative measurement of myocardial enzymes and elevation of cardiac biomarkers such as troponins and creatine kinase‐myocardial band, leading to higher mortality during the perioperative period . Cardiologists have indicated that several factors affect the occurrence of PMI, including the formation of distal embolism, side‐branch occlusion, coronary artery dissection, disruption of collateral flow, inflammation, and mixed pathological mechanisms …”
Section: Introductionmentioning
confidence: 99%